METROLOGICAL SUPPORT OF GEODETIC WORKS IN THE ROAD ROUGHNESS MEASURING: Array - Sarkisian, H.; Tymoshevskyi, V.; Urdzik, S. (Municipal economy of cities. Series: «Economy science», 2021)
Most of the transport and operational indicators that directly affect the road roughness depend on the roughness of coverage. Therefore, the control and timely monitoring of the road roughness is an extremely important issue that needs the attention of road maintenance services. At monitoring of the road roughness it is most expedient to use a technique of leveling of a covering. The method of leveling the coating provides more detailed information about the coating and allows you to determine the smallest deformations on the road coating, which may be at the first stage of their development, especially at that stage of their development, and show roughness and various parameters. One of the main tasks of measurements in the process of performing geodetic works is not only to obtain the measurement result, but also to assess its reliability. The required quality of instrumental measurement can not be achieved without adhering to the principles of unity and the required accuracy of measurements, so much attention should be paid to the metrological support of geodetic works. The purpose of this article is to analyze the metrological support of geodetic works in determining the pavement roughness and substantiation of the required accuracy of measuring the non-rigid pavement roughness. On the basis of dependences for determining the coefficient of dynamic load on pavement and the correlation between the pavement roughness and the coefficient of dynamic load and on the basis of experimental data, the necessary accuracy of measuring the non-rigid pavement roughness is substantiated. Based on the analysis, it was found that the accuracy of determining the height of the irregularities should not exceed 0.5 mm, for which it is necessary to use optical or electron-optical levels.